2022
DOI: 10.3390/su14095489
|View full text |Cite
|
Sign up to set email alerts
|

Status of Pesticide Usage on Golf Courses in Korea and Optimal Pesticide Usage Plan

Abstract: Risks to human health and the environment owing to pesticide usage have arisen interest, increasing the demand for reducing pesticide consumption used on golf courses. However, standard guidelines or manuals for reducing pesticide usage on golf courses in Korea are lacking. Herein, the trends of pesticides on golf courses were investigated, and the optimal pesticide usage plan was proposed for continuous pesticide reduction. In 2019, there were 539 golf courses in Korea. With the increasing number of golf cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Law and regulation are the most direct ways to change the behavior of farmers [14,15]. However, Lichtenberg showed that the impact of government regulation on farmers' pesticide use behavior is relatively limited due to the dispersion of farmers.…”
Section: Introductionmentioning
confidence: 99%
“…Law and regulation are the most direct ways to change the behavior of farmers [14,15]. However, Lichtenberg showed that the impact of government regulation on farmers' pesticide use behavior is relatively limited due to the dispersion of farmers.…”
Section: Introductionmentioning
confidence: 99%